Marx and the critique of capitalist society: critique of labor/Marx e a crítica ontológica da sociedade capitalista: crítica do trabalho - Mario Duayer (Em Pauta: Teoria Social e Realidade Contemporânea, 2012)
The paper seeks to emphasize what in my opinion can be consideredthe main thrust of Marxian work: the critique of political economy as an ontological critique of the modern capitalist society. Such critique begins to take its ultimate form with the Grundrisse. The argument runs as follows. Firstly, it tries to show briefly the debilitating effects, both in theory and practice, brought about in the last decades by the dissolution of the Marxian ontological critique. Secondly, it argues that real critique is ontological critique and, consequently, has to explain what such a critique consists of. Finally, agreeing with Postone’s suggested reinterpretation of Marx’s ideas, but diverging from him precisely with respect to ontology, it suggests that the ontological critique produced by Marx is a critique of labor or, in other words, critique of the centrality of labor, which is specific of the capitalist society.O artigo pretende destacar o que constitui para mim o propósitocentral da obra marxiana que, nos Grundrisse, começa a tomar forma acabada,a saber, a crítica da economia política como crítica ontológica da modernasociedade capitalista. O argumento está assim estruturado. Em primeiro lugar,inicio procurando mostrar de maneira sintética os efeitos paralisantes, teóricose práticos, da dissolução da crítica ontológica marxiana nas últimas décadas.Em segundo lugar, e justamente por isso, tento sustentar que crítica de fato écrítica ontológica e, em consequência, devo mostrar de que se trata essa crítica.Por último, concordando com a interpretação da obra de Marx proposta porMoishe Postone, mas diferindo dela precisamente no que diz respeito à onto-logia, procuro demonstrar que a crítica ontológica elaborada por Marx é críticado trabalho, ou, caso se queira, crítica da centralidade do trabalho, própria eespecífica da sociedade capitalista.